A Comparison of Work-Exacerbated Asthma Cases from Clinical and Epidemiological Settings - Paul K Henneberger; Xiaoming Liang; Catherine Lemière (Canadian Respiratory Journal)
BACKGROUND: Clinical and epidemiological studies commonly use different case definitions in different settings when investigating work-exacerbated asthma (WEA). These differences are likely to impact characteristics of the resulting WEA cases.